ESTABLISHMENT OF ORTHOMETRIC HEIGHT CONTROLS IN THE EASTERN PART OF KOGI STATE USING GNSS AND EGM 2008 - Negedu, Achimugu Amos; Ono, Matthew Nnonyelu (FUDMA JOURNAL OF SCIENCES, 2024)
The aim of this study was to model the orthometric heights in parts of Kogi East, Kogi State using GNSS and EGM 2008 with the objectives of establishing the best geoid undulation for height determination. The Hardwares used for this study include; Hi target V.30 dual frequency GNSS receiver and its accessories, Data logger, Computer hardware and software and Computer – HP Laptop and internet facilities. Softwares used included; Arc GIS, Google map, microsoft word, Microsoft excel, Hi target Geomatic offices, CSRS – PPP website andGeoid Eval Calculator. GNSS observations were conducted on 6 station monument. The dual frequency v30 Hi target instrument was used in the static mode to make observations on all the established points at an epoch rate of 30 seconds; for a period of one hour to one hour thirty minutes (session) per station. The secondary data were the EGM 2008, obtained from Geoid eval platform in https://www.geographiclib.sourceforge.ion/cgi-bin/GeoidEval. Geoid Eval platform makes provision for the geographical coordinates to be inputed before the geoidal-ellipsoidal separation values can be provided. Geoid Eval computes the height of the geoid above the WGS 84 ellipsoid using interpolation in a grid of values for the earth gravity models. To obtain the orthometric height, the geoid value is subtracted from the ellipsoidal height obtained from the GNSS-PPP observation. The accuracy of the geoid value is 1mm and that of the GNSS-PPP was adjudged to be 3cm respectively. It was recommended that, more orthometric heights be distributed for monitoring of the earth’s dynamisms.